PENGARUH PENGGUNAAN MEDIA DIGITAL KANTONG PERKALIAN TERHADAP HASIL BELAJAR MATERI OPERASI PERKALIAN SISWA KELAS II SD NEGERI 141 PEKANBARU - Annisa Miftahul Jannah Annurnas; Siti Quratul Ain (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to determine the effect of using the Digital Multiplication Pocket Media on students’ mathematics learning outcomes in multiplication operations for second-grade students at SD Negeri 141 Pekanbaru. The study employed a quantitative approach with a pre-experimental method using a One Group Pretest-Posttest Design. The sample consisted of 30 students from class II B selected through purposive sampling. Data were collected through tests, observations, and documentation. Data analysis was conducted using the normality test, Paired Sample t-Test, and N-Gain test. The results showed that the mean pretest score of 56.07 increased to 78.40 in the posttest. The data were normally distributed, and the Paired Sample t-Test yielded a significance value (Sig. 2-tailed) of 0.000 < 0.05 with a t-value of -7.505, indicating a significant difference between the pretest and posttest scores. The N-Gain test resulted in an average score of 0.53, which falls into the moderate category. Therefore, it can be concluded that the use of Digital Multiplication Pocket Media has a positive and significant effect on the mathematics learning outcomes of second-grade students at SD Negeri 141 Pekanbaru.